Fatigue and recovery-related changes in postural and core stability in sedentary employees: a study protocol - Amiri, Banafsheh; Zemková, Erika (Frontiers in Physiology, 2024)
Prolonged sitting leads to a slumped posture, which indirectly influences spinal curvature and increases low back and hamstring stiffness. Active rather than passive recovery is an effective way to reduce the risks associated with such prolonged inactivity. However, it remains to be investigated which of the exercises frequently used for this purpose, the trunk stability and foam rolling exercise, is more beneficial. This protocol study will compare the effects of foam rolling exercises on the recovery of impaired core and postural stability induced by core muscle fatigue and hamstring muscle stiffness with those of trunk stabilization exercises in sedentary adults. Twenty sedentary adults ranging in age from 25 to 44 years old, comprising 50% men and 50% women, will participate in a modified Abt’s trunk muscle fatigue protocol, then proceed with (1) active recovery in the form of trunk stabilization exercises, (2) active recovery in the form of foam rolling exercises, and (3) passive recovery, entails lying on a bed, respectively. Pre-fatigue, post-fatigue, and after all three recovery modalities, core and postural stability, and back and hamstring muscle flexibility will be evaluated using an inertial sensor system, and a posturography system. Muscle-fatigue conditions will be determined using electromyogram signals. Although the effects of foam rolling and trunk stabilization exercises can be attributed to different physiological mechanisms, the former releasing myofascial to improve flexibility and reduce muscle tension, the latter strengthening core muscles to stabilize posture, we hypothesize that both are equivalently effective in reducing the consequences of prolonged sitting.